"ON–OFF–ON" fluorescent probes based on nitrogen-doped carbon dots for hypochlorite and bisulfite detection in living cells. Issue 23 (30th October 2018) - Wang, Ruoming; Wang, Ruixia; Ju, Dongyan; Lu, Wei; Jiang, Chunzhu; Shan, Xueru; Chen, Qian; Sun, Guoying
Abstract : A fluorescent probe based on N-CDs was synthesized by a solvothermal method to detect ClO − and HSO3 − in cells through an "ON–OFF–ON" mode. Abstract : Although hypochlorite (ClO − ) and bisulfite (HSO3 − ) play important roles in the biological immune system and the aging process of living organisms, they are also classified as a third type of carcinogens. Hence, a convenient and efficient method to monitor ClO − and HSO3 − in ecological environments is highly desired. In this article, an "ON–OFF–ON" fluorescent probe based on nitrogen-doped carbon dots (N-CDs) for the detection of ClO − and HSO3 − has been demonstrated successfully. Because of the destruction of the surface passivation layer, the fluorescence of the N-CDs was quenched by ClO − . Furthermore, the quenched fluorescence of the N-CDs was restored efficiently through the increase in conjugation from the attached sulfo groups, indicating the feasibility of ClO − and HSO3 − detection. This fluorescent probe exhibited excellent sensitivity and selectivity to ClO − and HSO3 − detection with the limits of detection (LODs) of 3.4 μM and 0.27 μM in aqueous solution, respectively. In addition, the as-prepared N-CDs were successfully applied to detect both ClO − and HSO3 − in living cells due to their low toxicity and fast response speed.